2005
DOI: 10.1074/mcp.m500209-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Human Platelet Membrane Proteome Reveals Several New Potential Membrane Proteins

Abstract: We present the first focused proteome study on human platelet membranes. Due to the removal of highly abundant cytoskeletal proteins a wide spectrum of known platelet membrane proteins and several new and hypothetical proteins were accessible. In contrast to other proteome studies we focused on prefractionation and purification of membranes from human platelets according to published protocols to reduce sample complexity and enrich interesting membrane proteins. Subsequently protein separation by common one-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
134
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 47 publications
6
134
0
1
Order By: Relevance
“…Many drug targets are membrane proteins, and thus there is considerable interest in the plasma membrane subproteome. 122 Dedicated studies used gel-based 99,103,123 or gel-free 108 approaches, with the latter yielding ≈650 membrane proteins, identifying even low abundant 7 transmembrane domain receptors, such as the P2Y 1 receptor for ADP (≈150 copies per platelet). These studies clearly extended our knowledge of plasma membrane proteins and receptors.…”
Section: Platelet Subproteomesmentioning
confidence: 99%
“…Many drug targets are membrane proteins, and thus there is considerable interest in the plasma membrane subproteome. 122 Dedicated studies used gel-based 99,103,123 or gel-free 108 approaches, with the latter yielding ≈650 membrane proteins, identifying even low abundant 7 transmembrane domain receptors, such as the P2Y 1 receptor for ADP (≈150 copies per platelet). These studies clearly extended our knowledge of plasma membrane proteins and receptors.…”
Section: Platelet Subproteomesmentioning
confidence: 99%
“…Very recently, the integration of proteomic, genomic, and bioinformatic data of platelets has been applied in order to obtain a better understanding of platelet functions in health and disease [140,155,156]. Several reviews related to different aspects of platelet proteomics have been reported [157][158][159][160][161][162][163][164].…”
Section: Plateletsmentioning
confidence: 99%
“…The 1-DE can be combined with many chromatographic techniques such as RP separation of proteins, and has proved to be very successful in the analysis of complex membrane proteins. Cao et al [68] analysed isolated PM proteins using SDS-PAGE and microcapillary RP LC-MS/MS to identify 428 proteins, including 204 integral membrane or membraneassociated proteins.…”
Section: Modern Strategies For the Expression And Functional Proteomimentioning
confidence: 99%